Analitik ağ süreci ve promethee teknikleri ile hastane yer seçimi : Trabzon örneği - İmamoğlu, Gül (Fen Bilimleri Enstitüsü, 2015)
Nüfus artışı, ortalama yaşam süresinin uzaması, değişen beslenme alışkanlıkları, salgın hastalıkların geniş bölgelere hızla yayılması gibi sebeplerle dünya genelinde sağlık sektörüne olan talep gün geçtikçe artmaktadır. Bu talep artışı sağlık sektörünün bel kemiği konumunda olan hastanelere duyulan ihtiyacı da arttırmaktadır. Türkiye, kişi başına düşen hastane yatak sayısı ve kişi başına düşen doktor sayısı gibi hususlarda Avrupa ülkelerinin gerisindedir. Hem bu eksikliği gidermek hem de artan sağlık taleplerini karşılamak için Türkiye'de yeni hastaneler kurulmasına büyük önem verilmektedir. Hastanelerin etkili bir şekilde toplum sağlığına katkı verebilmesi, çevre ile uyumlu olması ve sürdürülebilir başarı sağlaması için yer seçimi hayati önem taşımaktadır. Buna rağmen hastanelerin yer seçimleri üzerine yapılmış çalışmalar oldukça azdır. Hastaneler için uygun yer seçiminin belirlenmesi basit bir karar problemi değildir. Bu karar alınırken birçok etmenin değerlendirilmesi gerekmektedir. Hastaneler için uygun yer seçimlerinin yapılabilmesi, ancak geniş araştırmalar sonucu elde edilen verilerin kullanıldığı, rasyonel ve sayısal değerlendirme sistemlerinin uygulanması ile sağlanabilir. Trabzon ili, hem il içerisinde ikamet eden kişilerin hem de sağlık turizmi için ile gelen kişilerin oluşturduğu büyük sayıda hasta potansiyeline sahiptir. İl içerisindeki mevcut hastaneler ise giderek artan bu potansiyel hastaları karşılamakta zorlanmaktadır. Bu sebep ile Trabzon, özellikle son yıllarda yeni hastanelerin kurulduğu ve kurulmaya devam edilmesinin planlandığı bir şehir haline gelmiştir. Kurulacak hastanelerin etkili bir şekilde çalışmalarını sağlamak amacı ile Trabzon ili içerisinde yeni kurulacak bir hastane için en uygun ilçenin seçilmesine yönelik melez bir Çok Ölçütlü Karar Verme modeli sunulmuştur. Her karar modelinin içerisinde bulunduğu sistemin farklı özelliklerine göre modellenmesi uygun olacağından, uygulamanın yapıldığı Trabzon ili için belirleyici olacak kriterler saptanmıştır. Kriter ağırlıklarının Analitik Ağ Süreci (AAS) ile belirlendiği ve değerlendirmenin PROMETHEE Tekniği ile yapıldığı bu melez yöntem ile Trabzon ilindeki ilçeler hastane kurulmasına uygunluğuna göre sıralanmıştır. Elde edilen sıralamada özellikle ilk üç sırada yer alan ilçelerin uygun olma, son sırada yer alan ilçenin uygun olmama sebepleri irdelenmiş, ilçelerin üstün ve zayıf olduğu kriterlere dikkat çekilmiştir.

Demand for the health sector is increasing day by day in the worldwide because of many reasons such as continuous population growth, prolongation of life expectancy, changes in dietary habits, rapid spread of epidemic diseases over large areas and so on. This increasing demand for health sector causes rise in the need for hospitals which took place the most critical point in health sector. Turkey is behind of European Countries on issues such as number of hospital beds per head and number of doctors per head. Both to overcome this deficiency and to meet the growing health demands, great importance are given to establishment of new hospitals in Turkey. If hospitals are organized in an inefficient way it will reduce hospitals positive impact on public health. One of the key elements in hospital efficiency is the location selection. The location of the hospital is vitally important to contribute effectively to public health and be compatible with the environment. Also determining appropriate location will attract large amount of potential patients so this will affect the hospital’s business success. Nevertheless, academic studies for hospital location selection are quite limited. In addition to this situation, governments seem not to focus on this decision problem adequately. Determining the appropriate location for hospitals is not a simple decision making problem, which requires evaluation of many factors. An improper hospital location selection causes not only great financial responsibilities but also loss of human life. Suitable location selection for hospitals can be made only with using data obtained from extensive researches and implementation of rational and quantitative evaluation systems. Multi Attribute Decision Making (MADM) techniques are very useful techniques due to the ability of assessment multiple conflicting criteria. With this feature MADM techniques are suitable for hospital location selection problems. The aim of this study is to propose a decision making model for hospital location selection in the city of Trabzon. Trabzon province has a large number of potential patients from both people residing in the province and people who come to the city for medical tourism. The existing hospitals in the province are struggled to meet these increasing potential patients. For this reason, Trabzon has become a city where the new hospitals constructed in recent years. Furthermore, it is planned to continue establishment of new hospitals and therefore, Trabzon is determined as the application area. For this purpose, two of MADM techniques were combined to find appropriate location of hospital in Trabzon. Analytical Network Process (ANP) and PROMETHEE were used in the construction of the decision making model. xx In the decision model, alternatives were determined as Trabzon’s districts. There are eighteen districts in Trabzon and all of them are candidate places for hospital construction. After that, fourteen criteria were identified which were considered effective for this decision model. Because of those criteria affect each other, ANP is used when determining criteria weights for its ability of representing dependencies and feedbacks. Since fourteen criteria can not be made pairwise comparison, these criteria clustered into 4 groups. For calculation of criteria weights pairwise comparison values which obtained from several expert opinions, were entered to Super Decisions Program as data and criteria weights obtained from the program. Decision matrix was constructed by determining the value of each district on the basis of each criterion. When determining the value of each district on the basis of each criterion, different types of data were used. For some criteria raw data, for some others, values that are determined from specific calculations, and for the rest values that are determined from experts’ opinion were used. For ranking the alternatives PROMETHEE Technique was used. PROMETHEE was chosen because of its capability of including criteria’s features to decision model by using preference function. According to criteria’s specifications, preference functions, indifference thresholds and preference thresholds were determined for each individual criterion. And then Visual PROMETHEE program detected the ranking of alternatives. Akçaabat, which is one of the biggest district of Trabzon, took first place in obtained ranking for eligibility of hospital establishment. Even though this district has one public hospital and two private hospitals, because of its excess of population and centrality, Akçaabat district needs another public hospital. Akçaabat is also the district with the highest population density. This result was supported by existing hospital’s intensive working state. Ortahisar is the center district of Trabzon and has two public hospitals, two branch hospitals and two private hospitals. However because of Ortahisar is the most populated and the most central district of Trabzon, it is still suitable for establishment for a new hospital. Even though Ortahisar’s intensive need for hospital due to the factors of population and centrality, it took second place in the ranking because of its unsuitable situation comes from traffic density and very high cost of land. The Of district, took third place in the ranking because of its relatively high population, suitable situation according to environmental factors and having average value in other criteria. The Çaykara district, despite its low population, population density and centrality, has one public and one branch hospital. For this reason there is no need for a new hospital in the district. As a result of these, Çaykara took last place in the ranking. The district Düzköy took seventeenth place because of its low population, distance to main roads and even so having a public hospital. The district Köprübaşı took sixteenth place because of its low population, distance to main roads and high cost of land. In this thesis it is focused on hospital location selection which is not a popular topic on academic studies despite its importance. Both the proposed method being hybrid xxi and using a technique which is unused in the literature on this subject, can be considered as the specialty of this study.
Hospital location selection with analytic network process and Promethee techniques: The case of Trabzon
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Keywords: Analitik ağ süreci (ANP); Hastaneler; Planlama; Türkiye; Trabzon; Analytic network process (ANP); Hospitals; Planning; Turkey; Trabzon